2013
DOI: 10.1021/ja311058q
|View full text |Cite
|
Sign up to set email alerts
|

Thiolates Chemically Induce Redox Activation of BTZ043 and Related Potent Nitroaromatic Anti-Tuberculosis Agents

Abstract: The development of multidrug resistant (MDR) and extensively drug resistant (XDR) forms of tuberculosis (TB) has stimulated research efforts globally to expand the new drug pipeline. Nitro aromatic compounds, including 1, 3-Benzothiazin-4-ones (BTZs) and related agents, are a promising new class for the treatment of TB. Research has shown that the nitroso intermediates of BTZs that are generated in vivo cause suicide inhibition of decaprenylphosphoryl-β-D-ribose 2′ oxidase (DprE1), which is responsible for cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
97
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 61 publications
5
97
0
3
Order By: Relevance
“…The regeneration of TSC-NO 2 in the futile cycle is consistent with the depletion of GSH by low concentrations of TSC-NO 2 . Another probable mechanism that operates in aerobic conditions is the alkylation of GSH, as described for nitrocompounds [45]. In this regard, this mechanism could operate for the other studied TSC compounds that is consistent with significant GSH depletion only at concentrations ≥ 50  μ M. The present study provided considerable insight into the mechanisms by which these TSC-derivatives exert their effects, and these investigations should be continued in future specific and detailed studies.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The regeneration of TSC-NO 2 in the futile cycle is consistent with the depletion of GSH by low concentrations of TSC-NO 2 . Another probable mechanism that operates in aerobic conditions is the alkylation of GSH, as described for nitrocompounds [45]. In this regard, this mechanism could operate for the other studied TSC compounds that is consistent with significant GSH depletion only at concentrations ≥ 50  μ M. The present study provided considerable insight into the mechanisms by which these TSC-derivatives exert their effects, and these investigations should be continued in future specific and detailed studies.…”
Section: Resultssupporting
confidence: 67%
“…This putative mechanism is inspired by the mechanism proposed by Tiwari et al [45] for the formation of nitroso-intermediates of nitroaromatic compounds with antituberculosis (TB) activity. Nitroaromatic compounds, such as 1,3-benzothiazin-4-ones (BTZs) and similar compounds, generate nitroso-intermediates in vivo that are able to cause suicide inhibition of decaprenylphosphoryl- β -D-ribose 2′ oxidase (DprE1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, cine addition of either thiolate from the active site cysteine of DprE1 or hydride from a cofactor FADH 2 may be responsible for the generation of the nitroso intermediate at the enzyme active site. 10 It should be noted that in the absence of the enzyme, such nitroso intermediates, undergo dimerization or subsequent reduction (s) to hydroxylamines and amines. 10 We envisioned that the substitution of the nitro group of the 1,3-benzothiazinone scaffold by an electron withdrawing azide group (3, Figure 1) could result in a similar mode of activation and/or inhibition because the first nucleophilic step of a cine addition by either the thiolate from the essential cysteine or hydride from FADH 2 would still occur similar to that shown in Figure 2B.…”
Section: T Uberculosis (Tb) Is a Disease Mainly Caused Bymentioning
confidence: 99%
“…For example, DNBA analogs that were prepared by replacing a nitro group by trifluoromethyl or amide by sulfonamide possessed coccidiostatic activity [31,36,55]. A study of DNBA anion-radical analogs showed that active compounds had characteristically increased unshared electron density in the 6-position [56 -58].…”
mentioning
confidence: 99%